2008
DOI: 10.1002/ajmg.b.30705
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of the COMT gene polymorphism (Val158Met) on verbal working memory functioning in a healthy population

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 33 publications
(44 reference statements)
4
52
0
1
Order By: Relevance
“…Notably, the association of COMT Val158Met and cognitive function was reported to be dependent on ethnicity. In Caucasians, the Met allele was reported to be associated with better cognitive function (Bruder et al 2005;Aguilera et al 2008). Conversely, studies of East Asian samples indicated that the Val allele is associated with better cognitive function (Cheon et al 2008;Yeh et al 2009;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 87%
“…Notably, the association of COMT Val158Met and cognitive function was reported to be dependent on ethnicity. In Caucasians, the Met allele was reported to be associated with better cognitive function (Bruder et al 2005;Aguilera et al 2008). Conversely, studies of East Asian samples indicated that the Val allele is associated with better cognitive function (Cheon et al 2008;Yeh et al 2009;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 87%
“…No association between COMT and any cognitive measures 42 or unaffected relatives. 40 Moreover, an interaction between the COMT Val 158 Met polymorphism and the MTHFR C677T mutation on WCST performance has been found in patients with schizophrenia, with COMT Val/Val carriers who had at least 1 copy of the MTHFR T allele making more perseverative errors.…”
Section: Wisconsin Card Sorting Test (Wcst)mentioning
confidence: 92%
“…40,64 In healthy individuals, the Val/Val and Val/Met genotypes have been associated with worse performance in terms of commission errors, 47 context processing 44 and reaction time variability in some studies, 55 whereas other studies reported no association. 23,40,42,64 This inconsistency may be related to the use of different versions of the CPT across studies (for details about the different versions of the tasks used, see Appendix 1, Table S1). Interestingly, 1 study reported an interaction between the COMT Val 158 Met polymorphism and the DAT 40 bp variable number tandem repeat; participants homozygous for both the COMT Val allele and the DAT 10 allele exhibited worse performance in terms of commission errors.…”
Section: Continuous Performance Test (Cpt)mentioning
confidence: 99%
“…The catechol-O-methyltransferase (COMT ) gene codes for an enzyme that metabolizes catecholamines and it is particularly important for metabolizing prefrontal dopamine. A single point mutation in the COMT gene (val158met) is associated with differences in cognitive abilities (de Frias et al, 2004;Bruder et al, 2005;Bertolino et al, 2006;Aguilera et al, 2008;Stokes et al, 2011;Buckert et al, 2012). There is also some evidence that COMT genotype has a significant effect on the volume of gray matter and parietal lobe activity (Dumontheil et al, 2011).…”
Section: Mechanisms Of Tdcsmentioning
confidence: 99%